Demografia e distribuição da diversidade genética dos maiores felinos das américas (Puma concolor e Panthera onca) em fragmentos de mata atlântica - Souza, Andiara Silos Moraes de Castro e (2015)
The intense destruction of the environment contributed to the decline and isolation of wild populations, providing an intensification of genetic drift and inbreeding effects. These factors reduce the ability of individuals to adapt to environmental changes, making them more vulnerable to extinction. The two largest predators of the Americas, the cougar (Puma concolor) and jaguar (Panthera onca) are animals which are threatened by the reduction and fragmentation of habitats, especially in the Atlantic Forest, which is one of the most degraded biomes in the world due to human actions. The present study aimed to investigate both demographic parameters and the distribution of the genetic diversity of cougar and jaguar populations within Atlantic Forest remnants. The chosen areas (Serra da Mantiqueira, Serra do Mar continuous and Iguaçu National Park) are among the most important for the conservation of these cats. Mostly non-invasive samples (feces and hair) were collected in protected areas present in those remaining. The depositor species was confirmed by amplification of the ATP6 gene and the samples were individualized using microsatellite loci, which were also employed in population analyses. The sex of the individuals was determined using a small fragment of amelogenin gene. The results suggest that at least seven individuals of jaguars (4F:3M) inhabit the Iguaçu National Park and 12 (5F:7M) are present in the Serra do Mar continuous. These populations seem to be different, with evidence of low gene flow between them (lack of migrant and mixed individuals and pairs of highly related individuals). In Iguaçu is also estimated to exist at least seven cougars (3F:4M), also four (1F:3M) in the Serra da Mantiqueira and 14 (5F:9M) in the Serra do Mar continuous. Genetic structure was detected in this species, but evidencing gene flow maintenance between two detected populations (sign of migrants and mixed individuals and predominantly non related individuals). In both species high genetic diversity could be observed. This study obtained critical information and still unknown, about the demographic and structure of jaguar and cougar populations in the Atlantic Forest remain. These data will provide substantial information that can be used in monitoring, as well as being crucial and decisive in the increase of effective strategies for the conservation of these species.